Pemetaan Pola Sebaran Spasial Kedalaman Muka Air Tanah Dangkal Di Dataran Aluvial Limboto - Mansur, Suprianto; Nurfaika, Nurfaika; Lahay, Rakhmat Jaya (-, 2025)
The Limboto-Gorontalo Alluvial Plain is important because it serves as the centre of settlement, development, and economic growth in Gorontalo Regency. This research aims to map the depth of shallow groundwater in Limboto alluvial plain and to know the spatial distribution of shallow groundwater depth in Limboto alluvial plain. The method used in this research is descriptive quantitative method with survey approach to analyse the spatial distribution pattern of shallow water table depth in Limboto Alluvial Plain. The results of groundwater depth mapping in Limboto, West Limboto, and Tabongo sub-districts, with categories of Shallow (0.39 - 2.33 metres), Medium (2.33 - 4.27 metres), and Deep (4.27 - 6.21 metres). As a result, the lowest depth was found in Haya-Haya Village (-0.03 metres) and the Deep category was found in Tabongo Barat Village (17.4 metres). These findings are very important for sustainable water resources management and can serve as a reference for policy makers and communities in planning land use effectively. As such, the results of this study are expected to support better water conservation and management efforts in the Limboto Alluvial Plain